Pengaruh Penggunaan Media Sosial dan Pembelajaran Kewirausahaan Terhadap Minat Berwirausaha - Sulfikar, Sulfikar; Ellyawati, Noor; Abu, Ilham (Educational Studies: Conference Series, 2024)
This study analyzes the influence of social media and entrepreneurship education on the entrepreneurial interest of Economics Education students at Mulawarman University. Using a descriptive method with a quantitative approach, data were collected from 100 students through questionnaires and analyzed using multiple linear regression. The results indicate that social media has a positive and significant effect on entrepreneurial interest, with a t-Count of 2.377 > t-table 1.984, and a significance value of 0.019 < 0.05. Additionally, entrepreneurship education positively and significantly affects entrepreneurial interest, with a t-Count of 6.746 > t-table 1.984, and a significance of 0.000 < 0.05. Simultaneously, the use of social media and entrepreneurship education significantly influences entrepreneurial interest, with an f- Count of 71.229 > f-table 3.09 and a significance of 0.000 < 0.05. The conclusion of this study is that both social media and entrepreneurship education, individually and together, play an important role in enhancing the entrepreneurial interest of students.